Economic Impact of Halal Tourism in non-Muslim Majority Countries: A Comparative Analysis of Singapore, Thailand, and the UK - Muhammad Azizurrohman; Sri Budi Cantika Yuli; Supiandi (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose: This study examines the economic contribution of halal tourism to the Gross Domestic Product (GDP) of Singapore, Thailand, and the United Kingdom, highlighting the significance of this market segment in non-Muslim majority countries.Method: Employing a quantitative research approach, the study utilizes multiple regression analysis to investigate the relationship between halal tourism variables (tourist expenditure, tourist arrivals, and policy implementation) and GDP. Data were collected from national tourism boards, government statistics, and relevant reports, with separate analyses conducted for each country to ensure a nuanced understanding.Result: The findings reveal a significant positive impact of halal tourism on GDP in all three countries. In Singapore, tourist expenditure and arrivals, supported by robust halal-friendly policies, substantially contribute to economic growth. Thailand shows similar positive effects, with significant contributions from tourist expenditure and policy implementation. The United Kingdom also benefits economically from halal tourism, particularly through increased tourist expenditure and the implementation of Muslim-friendly policies.Practical Implications for Economic Growth and Development: The study indicates that non-Muslim majority countries like Singapore, Thailand, and the United Kingdom can enhance their GDP by actively promoting and supporting halal tourism through targeted policies and infrastructure that cater to Muslim travelers.